Association of types of dietary fats and all-cause and cause-specific mortality: A prospective cohort study and meta-analysis of prospective studies with 1,148,117 participants - Mazidi, Mohsen (2020)
Background: Associations between dietary fats and mortality are unclear. Methods: We evaluated the relationship between quartiles of total fat, mono-unsaturated (MUFA), polyunsaturated (PUFA) and saturated fatty acid (SFA) consumption, and all-cause, coronary heart disease (CHD), stroke, and type 2 diabetes (T2D)-associated mortality in 24,144 participants from the National Health and Nutrition Examination Surveys (NHANES) 1999–2010. We added our results to a meta-analysis based on searches until November 2018. Results: In fully adjusted Cox-proportional hazard models in our prospective study, there was an inverse association between total fat (HR: 0.90, 95% confidence interval 0.82, 0.99, Q4 vs Q1) and PUFA (0.81, 0.78–0.84) consumption and all-cause mortality, whereas SFA were associated with the increased mortality (1.08, 1.04–1.11). In the meta-analysis of 29 prospective cohorts (n = 1,148,117) we found a significant inverse association between total fat (0.89, 0.82–0.97), MUFA (0.93, 0.87–0.99) and PUFA (0.86, 0.80–0.93) consumption and all-cause mortality. No association was observed between total fat and CVD (0.92, 0.79–1.08) or CHD mortality (1.03 0.99–1.09). A significant association between SFA intake and CHD mortality (1.10, 1.01–1.20) was observed. Neither MUFA nor PUFA were associated with CVD or CHD mortality. Inverse associations were observed between MUFA (0.80, 0.67–0.96) and PUFA (0.84, 0.80–0.90) intakes and stroke mortality. Conclusions: We showed differential associations of total fat, MUFA and PUFA with all-cause mortality, but not CVD or CHD mortalities. SFA was associated with higher all-cause mortality in NHANES and with CHD mortality in our meta-analysis. The type of fat intake appears to be associated with important health outcomes.